Unveiling the omics tapestry of B-acute lymphoblastic leukemia: bridging genomics, metabolomics, and immunomics - Yin Le; Shicong Zhu; Hongling Peng; Zhihua Wang (Scientific Reports)
Abstract Acute B-lymphoblastic leukemia (B-ALL) is a highly heterogeneous hematologic malignancy, characterized by significant molecular differences among patients as the disease progresses. While the PI3K-Akt signaling pathway and metabolic reprogramming are known to play crucial roles in B-ALL, the interactions between lipid metabolism, immune pathways, and drug resistance remain unclear. In this study, we performed multi-omics analysis on different patient cohorts (newly diagnosed, relapsed, standard-risk, and poor-risk) to investigate the molecular characteristics associated with metabolism, signaling pathways, and immune regulation in B-ALL. Our findings indicate that the PI3K-Akt signaling pathway is significantly enriched across all groups, highlighting its critical role in B-ALL pathogenesis and progression. Furthermore, metabolomic analysis revealed that lipid metabolism, ferroptosis, and glutathione metabolism are closely linked to disease progression. Notably, in relapsed patients, dysregulated lipid metabolism and the activation of antioxidant mechanisms may contribute to treatment resistance. Immune-related pathways, such as the complement system and coagulation cascade, were also significantly enriched in patients with B-ALL. This suggests that these pathways, alongside the PI3K-Akt pathway, play a role in forming the tumor microenvironment, thereby promoting disease progression and relapse. Based on these findings, this study provides novel potential therapeutic targets for the personalized treatment of B-ALL and lays the foundation for further development of PI3K-Akt pathway inhibitors and immunometabolism-targeted therapies.